GLOBALISASI TAREKAT SUFI DI ASIA TENGGARA (STUDI PERAN TAREKAT DALAM PENYEBARAN ISLAM DI INDONEESIA) - Abdulloh Hadziq; M. Muqronul Faiz (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2024)
Sufis played an important role in the spread of Islam, A. H. Johns said that Sufi nomads broadcast Islam in the Nusantara, as evidenced by the many local sources that attribute the introduction of Islam into the region to nomadic teachers and their Sufi characteristics. Sufi masters had attractive delivery skills, especially the compatibility of Islam with local Indonesian religious beliefs and practices at that time. In the forces of globalization marked by the development of steam and print technology, members of transregional Sufi brotherhoods known as tarekat, engaged in active competition across the Indian Ocean. They did so in the name of a broader orthodoxy. Snouck Hurgronje saw much to do with the exponential increase of Southeast Asian pilgrims due to the opening of the Suez canal in 1869 and the subsequent increase in steam shipping between Arabia and the centers of Singapore, Batavia, and Surabaya. Furthermore, there are many ulama (Javanese and Arabic) formed their own schools and succeeded in becoming centers for the spread of Islam. This research uses library research, which is a type of research that obtains data from collected from various literatures. This research shows that Tarekat has a religious authority that provides a significant role in the anti-colonial spirit and Islamic style in Indonesia which is nuanced sufistic and cultural. So this research strengthens the theory of the spread of Islam in Indonesia through Sufistic paths. Keywords : Tariqah, globalization, Indonesia